Disruptive innovation on websites: the case of Airbnb and Netflix - Mokhtar, Aida; Wahid, Norashikin (Communication and Media Centre (COMET), 2022)
The digital era has revolutionised the way businesses with low capital are organised marking their stark difference from previous, traditional ways of doing business. These new business models have given competition to traditional businesses of which some have refused to pivot with the times making them maintain old markets and old strategies. The theory of disruptive innovation espouses the idea of innovation-driven growth by having businesses embrace the attributes of Simplicity, Convenience, Accessibility, and Affordability in a market where the norm is to focus on complexity and high costs. This multiple case study examined the websites of Airbnb and Netflix framed by the theory of disruptive innovation and Saussure’s Semiotic theory. Both American brands are products of disruptive innovation as they provide services at competitive prices for the masses. Airbnb offers homestays for vacation rentals at various prices and Netflix offers a streaming of a wide range of award-winning TV shows, movies, anime, documentaries, amongst them through Internet-connected devices without including commercials and at a low price. The research study’s purpose was to identify whether and how the attributes of disruption innovation were communicated on the websites of Airbnb and Netflix using Saussure’s theory of semiotics that focused on signs, the signifier and signified. The results were that all four attributes were identified on the websites and used in similar and different ways with the main strategy to aim for the mass market through the inclusive strategy of marketing communication that covers all market segments.